The implementation of waqf planning and development through Islamic financial institutions in Indonesia - Sugianto Sugianto; Andri Soemitra; Muhammad Yafiz; Ahmad Amin Dalimunthe; Reza Nurul Ichsan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
There is assumption in the community that waqf are physically permanent, and handed over directly to Nazir, even though there are also cash waqf through Islamic financial institutions (IFI). The present research was conducted using a qualitative approach This study aims to analyze the implementation of waqf planning by waqif, waqf development by waqf bodies and the structuring of IFI products in Indonesia related to waqf. This study used a qualitative descriptive method using an online questionnaire to waqif and in-depth interviews with waqf institutions and IFI, then analyzed descriptively qualitatively. The results showed that the development of endowments through Islamic financial institutions are carried out by two methods; namely, the development of endowments initiated by LKS and are offered to Waqf Board, and the development of waqf was initiated and offered to LKS by the Waqf Board and the structure of the waqf products consists of two models. One model is not directly made specifically for waqf products, but is linked to the needs of Nazir who have collaborated, and the other one is that LKS products are specifically structured for endowments devoted to mobilizing endowments that are either self-structured by LKS or upon the request by Nazhir.